The Evaluation Study of Implementation National Standard Library for University (SNPPT) in Universitas Pembangunan Nasional “Veteran” East Java - A. Prathama; A. Kriswibowo (Nusantara Science and Technology Proceedings)
College libraries play an important role in the Tri Dharma of Higher Education action. General education, education up to community service. UPN "Veteran" Jawa Timur (UPNVJT) as one of the New State Universities (PTNB) in Indonesia since 2014 needs to improve itself to be higher. Likewise, the UPNVJT Library Unit is one of the universities that also needs to be followed and produced in order to provide better service. Through the Regulation of the Head of the National Agency of the Republic of Indonesia 13 of 2017 concerning National Standards for College Libraries (SNPPT) has determined how higher education must be carried out. This research is the first research conducted at UPNVJT to measure the achievement of SNPPT. The purpose of this study is to find the achievement of SNPPT in 2018. Data Collection Method. The research approach used is qualitative descriptive with data retrieval methods using interview techniques and observations on the object of research. Analysis Data. This study uses tabulation and interactive data analysis, models. Results and Discussions. The results of this study indicate that the UPNVJT Library already has SNPPT regulations. Implementation of SNPPT in 2018 has reached 76.6%. Conclusions. SNPPT management has been well implemented by the UPNVJT Library. However, it is necessary to make special improvements to the Standard Service section to benefit by adding librarian service hours.